The Concept of Moral Education in Islamic Perspective: A Theoretical and Practical Study - Siregar, Edy Saputra; Margolang, Saipul; Purba, Fitriadi; Purba, Muhammad Azam (Integrasi: Jurnal Studi Islam dan Humaniora, 2025)
Moral education in the Islamic perspective plays a vital role in shaping individuals with noble character based on the teachings of the Qur’an and Sunnah. This study aims to analyze the concept of moral education from both theoretical and practical perspectives, emphasizing its fundamental principles, objectives, and implementation in daily life as well as in formal and non-formal education. The method employed is a literature review with a descriptive-analytical approach, exploring the thoughts of classical and contemporary scholars on moral education. The findings reveal that moral education in Islam is not only oriented towards individual behavioral formation but also towards the development of a complete personality (insan kamil) capable of facing the challenges of globalization without losing Islamic identity. This research recommends strengthening moral education across various domains—family, school, and society—as a solution to the moral crisis faced by the younger generation.